Disparities in Perioperative Use of Patient Engagement Technologies - Not All Use is Equal. Issue 1 (9th January 2023) - Theiss, Lauren M.; Wood, Lauren; Shao, Connie; Marques, Isabel; Kim, Dae Hyun; Hollis, Robert; Gunnells, Drew; Hardiman, Karin; Cannon, Jamie; Morris, Melanie; Kennedy, Gregory; Chu, Daniel I.
Abstract : Objective: To determine the association of patient-level characteristics on the use of a patient engagement technology during the perioperative period. Summary of Background Data: As implementation of patient engagement technologies continues to grow, it remains unclear who uses, and not uses, these technologies. Existing literature suggests significant disparities in usage of other technologies by patient age, race, sex, and geographic location, however, have yet to characterize patient usage of patient engagement technologies. Methods: This is a retrospective cohort study of patients undergoing elective surgery by a colorectal surgeon between January 2018 and March 2020 who enrolled in a patient engagement technology at a single institution. Patients enrolled received educational content, healthcare reminders, patient reported outcome (PRO) surveys, and health checks preoperatively, in-hospital, and for 30-days postdischarge. The primary outcome was patient activation of the patient engagement technology. Secondary outcomes were completion of at least 1 PRO survey, 1 in-hospital health check, and 1 postdischarge health check. Results: Of 549 patients who enrolled in the patient engagement technology, 473 (86.2%) activated. On multivariable stepwise regression, female patients [odds ratio (OR) 2.4, confidence interval (CI) 1.4–4.0, P = 0.001] and privately insured patients (OR 2.0, CI 1.1–3.8, P = 0.03) were more likely to activate. Black patients were less likely to activate (OR 0.5, CI 0.3–0.9, P = 0.02). Once activated, privately insured patients were more likely to complete PRO surveys (OR 2.3, CI 1.2–4.3, P = 0.01), in-hospital health checks (OR 2.4, CI 1.4–4.1, P = 0.002), and postdischarge health checks (OR 1.9, CI 1.1 −3.3, P < 0.001) than uninsured patients. Black patients were less likely to complete PRO surveys (OR 0.4, CI 0.3-0.7, P = 0.001) and in-hospital health checks (OR 0.6, CI 0.4–0.9, P = 0.03) than White patients. Conclusions: Use of a patient engagement technology in the perioperative period differs significantly by sex, race/ethnicity, and insurance status. These technologies may not be used equally by all patients, which should be considered during implementation of interventions to improve surgical outcomes.